Pengujian Drying Conveyor Dengan Pemanfaatan Incinerator Pembangkit Listrik Tenaga Sampah - Rayhan Maulana; Marno; Iwan Nurgraha (Faculty of Engineering, Universitas Serambi Mekkah, 2024)
Waste management is a major challenge in Indonesia, with waste generation expected to reach 20.3 million tonnes per year by 2022. Karawang, West Java, is one of the areas with limited waste treatment capacity and infrastructure, with waste production reaching 900 tonnes per day and only 400 tonnes sent to landfill. This study aims to test the efficiency of waste drying using a conveyor dryer using heat from the incinerator. The research method used was an experimental trial with steps including collecting initial data, operating the dryer and analysing the drying results. Tests were carried out on several types of waste, namely vegetables (cabbage), fruit (oranges) and a mixture, to evaluate the reduction in water content and drying efficiency. The test results showed that the conveyor worked well at a temperature of 60°C and the components worked according to the settings. The drying efficiency varied between 16.67% and 56.90%, with an average water content reduction of 1.24 kg in 4 hours for cabbage vegetable waste. The drying process showed that the waste experienced a significant reduction in water content, depending on the type and weight of the waste.